Phosphorylation of histone H3Ser10 in plant cell division - D. B. Loginova; O. G. Silkova (Вавиловский журнал генетики и селекции)
Histones, the major protein components of chromatin, undergo post-translational modifications, which particularly affect the structural and functional organization of chromosomes. The most common post-translational modifications are phosphorylation, methylation, acetylation and ubiquitination. Histone phosphorylation occurs mainly at N-terminal tails of serines (Ser) and threonines (Thr), and coordinates various processes of mitotic and meiotic division. It has been shown that this type of modification is required for activation of transcription, DNA damage repair, recombination and also for chromosome condensation and segregation. Histone H3 is characterised by the presence of a large number of modification sites among the four core histones. In plants, phosphorylation of histone H3 at serine positions 10 and 28 and at threonine positions 3, 11, 32 and 133 is the most well studied. This review contains the most complete data on the spatial and temporal distribution of H3 phosphorylation of serine at position 10 (phH3Ser10) in mitosis and meiosis in different plant species. Most species are characterised by phosphorylation of the centromeric region in mitosis and second meiotic division, and by phosphorylation throughout the chromosomes in the first meiotic division. However, there are exceptions to the phH3Ser10 distribution in mosses and cestrum, as well as in species with holocentric chromosomes. There are contradictory data on the phH3Ser10 distribution in mitosis and meiosis in the same species. The functional significance of phH3Ser10 in cell division in plants is associated with the activity of the centromere, centromere cohesion and sister chromatid and chromosome segregation. We discuss the participation of currently known candidate kinases and phosphatases in the dynamics of H3Ser10 phosphorylation. The review provides an overview of the role of phH3Ser10 modification in the chromosome division and segregation in mitosis and meiosis.